2014
DOI: 10.1177/0097700414530830
|View full text |Cite
|
Sign up to set email alerts
|

Redefining the Chinese Revolution

Abstract: In recent years, China scholars have often debated the meaning and definition of the Chinese Revolution. While some studies reveal discontinuity or radical and transformative change, others show continuity or gradual and evolutionary change. This article contributes to the debate by examining how the connective tissues in Guizhou’s regional economic institutions—the regional economic bureaucracy and regional state enterprises as well as enterprise organization, management, and incentive structures and mechanis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Dose consistency among various meta-analyses including data from randomized clinical trials and observational (cohort) studies supports the 400-600 mg/d recommendation for cardiometabolic health. The Expert Panel also considered the European Food Safety Authority (EFSA) Panel on Dietetic Products, Nutrition, and Allergies' Scientific Opinions authorizing the health claim on consumption of cocoa flavanols and maintenance of normal endothelium-dependent vasodilation, and the specific proposed concentrations for proanthocyanidins and catechins by the Chinese Nutrition Society (22,23). Although the small effects exerted by flavan-3-ols on individual biomarkers (e.g., a 1 mm Hg decrease in systolic and diastolic blood pressure) might seem clinically insignificant in isolation, it has been noted that each 2-mmHg increase in systolic blood pressure increases mortality due to ischemic heart disease and stroke by 7% and 10%, respectively (24).…”
Section: Rationale and Supporting Evidence For The Recommendationmentioning
confidence: 99%
See 1 more Smart Citation
“…Dose consistency among various meta-analyses including data from randomized clinical trials and observational (cohort) studies supports the 400-600 mg/d recommendation for cardiometabolic health. The Expert Panel also considered the European Food Safety Authority (EFSA) Panel on Dietetic Products, Nutrition, and Allergies' Scientific Opinions authorizing the health claim on consumption of cocoa flavanols and maintenance of normal endothelium-dependent vasodilation, and the specific proposed concentrations for proanthocyanidins and catechins by the Chinese Nutrition Society (22,23). Although the small effects exerted by flavan-3-ols on individual biomarkers (e.g., a 1 mm Hg decrease in systolic and diastolic blood pressure) might seem clinically insignificant in isolation, it has been noted that each 2-mmHg increase in systolic blood pressure increases mortality due to ischemic heart disease and stroke by 7% and 10%, respectively (24).…”
Section: Rationale and Supporting Evidence For The Recommendationmentioning
confidence: 99%
“…For example, the recent scientific opinion from EFSA regarding the safety of green tea catechins concluded that there is evidence from clinical trials that intake of doses ≥800 mg EGCG/d taken in supplemental form can increase serum transaminases. Similarly, the Chinese Nutrition Society has proposed a 800 mg/d tolerable upper intake level for proanthocyanidins (23). As such, foods including tea, cocoa, cinnamon, apples, and berries should be prioritized over supplementation when seeking potential cardiometabolic benefits from flavan-3-ols.…”
Section: Potential Risks or Adverse Events Associated With Flavan-3-o...mentioning
confidence: 99%